Método de avaliação de jogos educacionais digitais através de heurística (AHJED) - Silva, Max André de Azevêdo (2019)
The process of creating digital educational games requires attention to the technical and pedagogical aspects. Such aspects may be the deciding factor between the success or failure of the game. Seeking to ensure a higher quality of these aspects, it is interesting to use the evaluation of educational games. One of the heavily used methods for this type of evaluation is the heuristic-based method. This method has been shown to be interesting for low cost and flexibility. There are proposals for heuristics to evaluate educational games, but these proposals demonstrate some points of possible improvements. In this way, this work presents a new heuristic evaluation model for digital educational games, in which it aims to propose a better evaluation of the technical and pedagogical aspects of digital educational games. For this, a systematic mapping was first carried out on the evaluation of educational digital games, afterwards a comparison was made between these techniques, soon after an experiment was carried out with a heuristic evaluation technique, later a new set of heuristics was proposed, to evaluate the technical and pedagogical aspects of digital educational games and, finally, validations of the proposed set were made.